Demographic variations and temporal trends in hospice and palliative care fellowship matches in the United States - Aman Goyal; Samuel L. Flesner; Urooj Shamim; Sonia Hurjkaliani; Priya Goyal; Mohamed Daoud; Amir Humza Sohail (Scientific Reports)
Abstract This study examines trends in application and match rates for the United States Hospice and Palliative Care Fellowship Match, focusing on demographic variations, competitiveness, and match success across applicant types. This retrospective study analyzed data from the National Resident Matching Program for Hospice and Palliative Care fellowships from 2016 to 2024, including applicant demographics and match outcomes. Chi-square tests were used to assess differences and temporal trends were evaluated with Mann–Kendall tests, and statistical significance was set at p < 0.05. Our results were that the number of fellowship programs increased from 122 in 2016 to 185 in 2024 (51.6% increase), with positions rising from 280 to 451 (61.1% increase). Applicants grew by 75.2%, from 259 to 454. US MDs had significantly higher match rates than non-US MDs (86.1% vs. 79.8%, p < 0.001). Female applicants were significantly overrepresented in Hospice and Palliative Care fellowships compared to all fellowships (64.9% vs. 47.0%, p < 0.001), while males were underrepresented (33.4% vs. 51.4%, p < 0.001). A higher proportion of matched applicants were from rural areas compared to all fellowships (16.0% vs. 13.1%, p = 0.040). In conclusion, the number of Hospice and Palliative Care fellowship programs, positions, and applicants has increased. Female applicants, compared to males, and White applicants, relative to their representation in all fellowships, accounted for a larger proportion of applications and had higher match rates. Heterosexual applicants were less likely to pursue Hospice and Palliative Care fellowships compared to all specialties.